Fifty Years of Library Literature on Ghana: A Bibliometric Study - Fosu, V.K.; Alemna, A.A. (Ghana Library Journal, 2002)
This paper presents an analysis of the structure and bibliographic control of the Ii terature on librarianship in Ghana during the period 1950-2000. Areas covered include number of publications by decade; format of publications; the major subjects covered; the most popular journals of publication; and the extent of usage of non-library science journals. The findings indicate among others, that the Ghana Library Journal has contributed immensely to library literature on Ghana. Implications of the study are also discussed.